Describing the determinants of problem gaming in South Africa : a longitudinal approach - Rosenberg, Samantha Claire (School of Economics, 2016)
In this study, an enhanced model describing the temporal determinants of problem gambling in South Africa is established using the National Longitudinal Study of Gambling Behaviour (NLSGB) dataset. Various conceptual ambiguities evidenced in the literature, particularly those associated with the Problem Gambling Severity Index (PGSI) screen, are explored. Gambling severity classification, as per the PGSI, is unstable over time. Evidence suggests that the standard PGSI cut-off score of 8 may be replaced by a score of 10 in some cases. For robustness, concurrent use of the PGSI and the Diagnostic and Statistical Manual of Mental Disorders (DSM) measurement criteria for problem gambling is advised. Although it remains undetermined whether problem gambling is best understood as an ordinal or a continuous disorder, the bounded natures of the PGSI and DSM scoring-systems make the statistical analyses of these tools most consistent with an ordinal structure; use of continuous structures cause statistical complications.